2005
DOI: 10.1158/1078-0432.ccr-05-1077
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis Correlates with Lymph Node Metastasis, Prognosis, and Angiogenic Phenotype in Human Non–Small Cell Lung Cancer

Abstract: Purpose: Recent experimental studies have revealed that lymphangiogenesis plays an important role in cancer progression, but its clinical significance in the case of non-small cell lung cancer (NSCLC) remains unclear. Our aim was to assess the lymphangiogenesis of human NSCLC, and to correlate this with angiogenic phenotype (angiogenic versus nonangiogenic growth pattern) and clinical behavior. Experimental Design: One hundred and three patients with NSCLC and complete follow-up information were included. Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
4
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 26 publications
(18 reference statements)
7
103
4
2
Order By: Relevance
“…Several studies have shown that peritumoral lymphatic vessels are associated with lymph node metastasis, 8,14,17,18,27,40,41 whereas other studies, only for head and neck squamous cell carcinoma, showed that intratumoral lymphatic vessels, and not peritumoral lymphatic vessel density, are important for lymphatic spreads. 3,14,15 Thus, we first examined the VEGF-C and D2-40 expression in cholangiocarcinoma S Aishima et al intratumoral or peritumoral lymphatic vessel density in intrahepatic cholangiocarcinomas, and detected the following: (1) lymphatic vessel density was much lower in the tumor center than in the tumor periphery; (2) lymphatic vessels in the tumor center were frequently collapsed, whereas peritumoral lymphatic vessels showed open lumen; and (3) lower lymphatic vessel density in the tumor center was significantly correlated with the presence of lymphatic invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that peritumoral lymphatic vessels are associated with lymph node metastasis, 8,14,17,18,27,40,41 whereas other studies, only for head and neck squamous cell carcinoma, showed that intratumoral lymphatic vessels, and not peritumoral lymphatic vessel density, are important for lymphatic spreads. 3,14,15 Thus, we first examined the VEGF-C and D2-40 expression in cholangiocarcinoma S Aishima et al intratumoral or peritumoral lymphatic vessel density in intrahepatic cholangiocarcinomas, and detected the following: (1) lymphatic vessel density was much lower in the tumor center than in the tumor periphery; (2) lymphatic vessels in the tumor center were frequently collapsed, whereas peritumoral lymphatic vessels showed open lumen; and (3) lower lymphatic vessel density in the tumor center was significantly correlated with the presence of lymphatic invasion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Several types of human cancer can induce the formation of lymphatic vessels, [3][4][5][6] whereas other cancers do not actively induce lymphangiogenesis and simply invade existing lymphatic vessels. [7][8][9][10][11][12][13] A positive relationship between the intratumoral or peritumoral lymphatic vessel density and lymphatic spreads has been reported in head and neck squamous cell carcinoma, 3,14,15 cutaneous melanoma, 16,17 lung cancer, 18 and pancreatic endocrine tumor. 19,20 Vascular endothelial growth factor-C (VEGF-C) has been found to be the common lymphangiogenetic factor, acting predominantly via VEGF receptor-3 (VEGFR-3), which is expressed by lymphatic endothelial cells, 21 and VEGF-C strongly promoted the growth of tumor-associated lymphatic vessels.…”
mentioning
confidence: 99%
“…Although it is claimed that LYVE-1 is a specific marker for lymphatic vessels, its value in identifying fully functional lymphatics, has been questioned. Two recent studies failed to detect lymphatics within the non-small-cell lung carcinoma using LYVE-1, 40,41 while were identified using podoplanin. 40 Another study was unable to detect LYVE-1 expression in the majority of the colorectal samples, but again showed podoplanin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies failed to detect lymphatics within the non-small-cell lung carcinoma using LYVE-1, 40,41 while were identified using podoplanin. 40 Another study was unable to detect LYVE-1 expression in the majority of the colorectal samples, but again showed podoplanin expression. 37 Therefore, LYVE-1 may not be expressed by functional lymphatics and stained nonfunctional intratumoral and peritumoral lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable assays to detect the presence of VEGF-C, VEGF-D and VEGFR-3, and also to detect intra-or peritumoural lymphangiogenesis must be in place. Approaches for detecting these by immunohistochemistry, including identification of lymphatic vessels by staining for markers such as LYVE-1 (Dadras et al, 2003) and podoplanin (Renyi-Vamos et al, 2005), have been described in the clinicopathological literature and may require further development to become sufficiently robust. Initial trials should be performed on cancers in which lymphangiogenesis can be detected in a reasonable proportion of cases.…”
Section: Targeting the Vegf-c/vegf-d/vegfr-3 Signalling Axismentioning
confidence: 99%